2001
DOI: 10.1016/s0925-4773(01)00532-9
|View full text |Cite
|
Sign up to set email alerts
|

Sequential expression of annexin A5 in the vasculature and skeletal elements during mouse development

Abstract: Annexin A5 (annexin V, anchorin CII) represents the prototype member of the large annexin family, characterized by its ability to interact with phospholipids in a calcium-dependent manner and to form calcium-specific ion channels. Despite intense biochemical analysis, the in vivo expression and function of this annexin during mouse development, still remains unclear. Immunohistochemistry, in situ hybridization and reporter gene expression were used to define expression of annexin A5 during early mouse developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…2C) also suggested that stability and internal organization of embryonic vascular basement membranes is perturbed. To test whether collagen IV deficiency also interferes with vascular development, we used the recently described Anxa5-lacZ transgene, which specifically detects perivascular cells, to visualize most blood vessels and capillaries in collagen IV mutant embryos (Brachvogel et al, 2001). β-gal staining demonstrated that the overall formation of the vasculature was indistinguishable between collagen IV mutant and wild-type embryos, as major vascular elements and the capillary networks in the embryo (Fig.…”
Section: Deficiency Of Collagen IV Results In Altered Basement Membramentioning
confidence: 99%
See 2 more Smart Citations
“…2C) also suggested that stability and internal organization of embryonic vascular basement membranes is perturbed. To test whether collagen IV deficiency also interferes with vascular development, we used the recently described Anxa5-lacZ transgene, which specifically detects perivascular cells, to visualize most blood vessels and capillaries in collagen IV mutant embryos (Brachvogel et al, 2001). β-gal staining demonstrated that the overall formation of the vasculature was indistinguishable between collagen IV mutant and wild-type embryos, as major vascular elements and the capillary networks in the embryo (Fig.…”
Section: Deficiency Of Collagen IV Results In Altered Basement Membramentioning
confidence: 99%
“…The Anxa5-lacZ fusiongene was generated by homologous recombination in ES cells and the derived mouse strain showed no obvious altered phenotype (Brachvogel et al, 2001;Brachvogel et al, 2003). By mating mice heterozygous for the Col4a1/2 mutation with Anxa5 lacZ/lacZ mice, a strain was established with Col4a1/2 +/-Anxa5 lacZ/lacZ genotype and used for generating embryos with various Col4a1/2 genotypes on a heterozygous Anxa5 lacZ/+ background.…”
Section: Visualization Of the Vascular System By The Use Of The Anxa5mentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies showed that this fusion gene is expressed in cells associated with the vascular network of embryos (E10.5-E14.5) (Brachvogel et al, 2001). To define the onset of expression during development, we analyzed Anxa5-lacZ + expression during early embryogenesis (E5.5-E9.5).…”
Section: Anxa5 Is Expressed During Early Stages Of Vasculogenesismentioning
confidence: 99%
“…Although numerous functions of annexin A5 have been described in vitro, its in vivo role still remains unclear (Brachvogel et al, 2003). Expression analysis of the annexin A5 gene (Anxa5) by the use of an Anxa5-lacZ fusion gene in vivo showed that this gene is expressed in vasculatureassociated cells and at later stages (E13.5-P1) in mesenchymal condensations, chondrocytes as well as all skeletal elements (Brachvogel et al, 2001).…”
Section: Introductionmentioning
confidence: 99%